Développe puis réduit ces expressions.
B = (x+9)(11-5x)
C = (2x-3)(2x+3)
E= (x+1)au carré +7x(2-x)
F= (x+3)(2x-1)- 3x(2x+5)
G = (4t + 1 )(4t -1) - (3t +2) au carré
H = 2(s + 5 )(s - 5 ) + (4s + 3 )au carré
I = (3x + 4 )au carré - (1 - 2x ) (6 + x)

2

Réponses

2013-10-13T17:58:45+02:00
B = (x+9)(11-5x)=11x-5x²+99-45x=-5x²-34x+99
C = (2x-3)(2x+3)=4x²+6x-6x-9=4x²-9
E = (x+1)²+7x(2-x)=x²+2x+1+14x-7x²=-6x²+16x+1
F = (x+3)(2x-1)-3x(2x+5)=2x²-x+6x-3-6x²-15x=-4x²-10x-3
G = (4t+1)(4t-1)-(3t+2)²=16t²-4t+4t-1-(9t²+12t+4)=16t²-4t+4t-1-9t²-12t-4=7t²-12t-5
H = 2(s+5)(s-5)+(4s+3)²=2(s²-5s+5s-25)+16s²+24s+9=2s²-10s+10s-50+16s²+24s+9=18s²+24s-41
I = (3x+4)²-(1-2x)(6+x)=9x²+24x+16-(6+x-12x-2x²)=9x²+24x+16-6-x+12x+2x²=11x²+35x+10
2013-10-13T18:04:30+02:00
B = (x+9)(11-5x)
= 11x-5x²+99-45x
= -5x²-34x+99

C = (2x-3)(2x+3)
= 4x²-9

E= (x+1)au carré +7x(2-x)
= x²+2x+1+14x-7x²
= -6x²+16x+1

F= (x+3)(2x-1)- 3x(2x+5)
= 2x²-x+6x-3-(6x²+15x)
=2x²-x+6x-3-6x²-15x
= -4x²-10x-3

G = (4t + 1 )(4t -1) - (3t +2)²
= 16t²-1-(9t²+12t+4)
=16t²-1-9t²-12t-4
=7t²-12t-5

H = 2(s + 5 )(s - 5 ) + (4s + 3 )au carré
= 2(s²-25)+16s²+24s+9
=2s²-50+16s²+24s+9
=18s²+24s-41

I = (3x + 4 )au carré - (1 - 2x ) (6 + x)
=9x²+24x+16-(6+x-12x-2x²)
=9x²+24x+16-6-x+12x+2x²
=11x²+35x+10